Friday night disability: The portrayal of youthful social interactions in television's Friday Night Lights - McGrail, Ewa; McGrail, J. Patrick; Rieger, Alicja (Disability Studies Quarterly, 2020)
Youth with disabilities negotiate social interaction with peers with several notable disadvantages in ableist culture. In addition, the characterizations of both real and fictional characters in mass media, particularly television, have an impact as well. However, youth with disabilities are significantly underrepresented in television series. Using the model of social relations by Alan Fiske and descriptive research design, we quantitatively examined the televisual characterization of a youth who acquires a disability in the television drama Friday Night Lights. We found that using the Fiskeian social model helped to uncover the social reality of disability as portrayed through youthful social interactions, which we closely tracked in the first season of this program. We situate this reality in the broader context of cultural narratives about disability in mass media.